2010
DOI: 10.1128/iai.00347-10
|View full text |Cite
|
Sign up to set email alerts
|

Avian-Pathogenic Escherichia coli Strains Are Similar to Neonatal Meningitis E. coli Strains and Are Able To Cause Meningitis in the Rat Model of Human Disease

Abstract: Escherichia coli strains causing avian colibacillosis and human neonatal meningitis, urinary tract infections, and septicemia are collectively known as extraintestinal pathogenic E. coli (ExPEC). Characterization of ExPEC strains using various typing techniques has shown that they harbor many similarities, despite their isolation from different host species, leading to the hypothesis that ExPEC may have zoonotic potential. The present study examined a subset of ExPEC strains: neonatal meningitis E. coli (NMEC)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

12
163
0
6

Year Published

2012
2012
2024
2024

Publication Types

Select...
4
3
2

Relationship

2
7

Authors

Journals

citations
Cited by 193 publications
(184 citation statements)
references
References 41 publications
(70 reference statements)
12
163
0
6
Order By: Relevance
“…This strengthens the hypothesis that chickens can act as a reservoir for ExPEC infection in humans (Adiri et al, 2003;Danzeisen et al, 2013;Ewers et al, 2007;Johnson et al, 2008c;Johnson et al, 2007;Kohler and Dobrindt, 2011;Rodriguez-Siek et al, 2005a;Tivendale et al, 2010).…”
Section: Public Health Significance Of Apecsupporting
confidence: 68%
See 1 more Smart Citation
“…This strengthens the hypothesis that chickens can act as a reservoir for ExPEC infection in humans (Adiri et al, 2003;Danzeisen et al, 2013;Ewers et al, 2007;Johnson et al, 2008c;Johnson et al, 2007;Kohler and Dobrindt, 2011;Rodriguez-Siek et al, 2005a;Tivendale et al, 2010).…”
Section: Public Health Significance Of Apecsupporting
confidence: 68%
“…Despite the difficulty in identifying the origin of human ExPEC, the genetic overlap reported globally between human ExPEC and avian E. coli suggests that APEC may be a zoonotic pathogen Mora et al, 2013;Moulin-Schouleur et al, 2007). The ability of APEC to cause disease in rats, in a study by Tivendale et al (2010), shows APEC can cause disease in mammals. A study in Denmark,…”
Section: Public Health Significance Of Apecmentioning
confidence: 99%
“…Isolates of E. coli that have caused neonatal meningitis in developed countries have been extensively studied (10,(14)(15)(16)(17)(18)(19). These studies have found that some serotypes and sequence types predominate among the E. coli strains that cause meningitis.…”
mentioning
confidence: 99%
“…Recent studies show marked structural similarities between APEC and human extraintestinal pathogenic E. coli (ExPEC) strains, suggesting that APEC may be a source of virulence genes for human ExPEC (10,11,12). These genomic similarities appear to translate to functional similarities, as certain APEC strains are able to cause disease in a rat model of human neonatal meningitis (26).…”
mentioning
confidence: 99%